2007
DOI: 10.1007/s00417-007-0597-2
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of delayed intervention when treating chemical eye burns

Abstract: Immediate emergency rinsing is essential in eye burn victims. Appropriate rinsing solutions and treatment facilities in the form of rinsing stations where chemical burns may occur must be available at the workplace. Tap water is also effective as a rinsing solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The advantage of immediate treatment has been demonstrated in the past by several studies 2–4 22 23. It has been shown that AMT benefits eyes with a low-grade chemical burn but this effect was not evident in eyes with severe injuries 24…”
Section: Discussionmentioning
confidence: 98%
“…The advantage of immediate treatment has been demonstrated in the past by several studies 2–4 22 23. It has been shown that AMT benefits eyes with a low-grade chemical burn but this effect was not evident in eyes with severe injuries 24…”
Section: Discussionmentioning
confidence: 98%
“…Animal studies have consistently demonstrated better outcomes when the eye is rinsed early and thoroughly after chemical exposure, 30,31 relating to the progressive neutralization of pH with water volume. Prolonged irrigation is best achieved using intravenous tubing and a polymethylmethacrylate (Morgan) lens, although when no such device is available, it is important to keep the eyelids retracted to assure adequate irrigation of the conjunctiva and cornea.…”
Section: Chemical Injuriesmentioning
confidence: 99%
“…8,16,17 Although these solutions are most commonly used because they are readily available, newer and more effective neutralising agents can be used. 8,[17][18][19] These agents include a balanced salt solution, Ringer's lactate, buffers and Diphoterine®.…”
Section: Ocular Lavagementioning
confidence: 99%